AKHLAK MEMINANG DAN WALIMATUL URSY MENURUT RIWAYAT ATAU DI PAHAMI DARI RIWAYAT PENDAPAT IMAM AT-TIRMIDZI - Irfan, Mhd. (SHAHIH (Jurnal Ilmu Kewahyuan), 2021)
Proposing marriage is the initial process in carrying out a marriage, so a prospective bride and groom must know the guidelines for proposing because many prospective brides and grooms make the wrong move. The sermon or proposal must be carried out in a manner that is in accordance with Islamic law because the aim of marriage is very sacred and has a far-reaching vision and mission. A person who is going to preach should not be complicated or make things difficult. This research aims to determine the ethics of proposing marriage and walimatul ursy according to the opinion of Imam At-Tirmidhi and to analyze the study of the book Sunan At-Tirmidhi and his opinions in its history. This type of research is library research. Data sources are divided into two parts. First, primary sources. This research uses qualitative research (Library Research) using primary sources, the Book of Sunan al-Jami al-Shahih At-Tirmidhi and secondary sources. Other supporting sources used by the author are supporting references in discussing this topic, including As-Sayyid Sabiq Fikih Sunnah, Hadiths about marriage ethics contained in Al-Minhaj Syarh Shahih Muslim where these references are used as reinforcement for the author's analysis. After conducting research, the author was able to collect several points that can be used as a basis regarding the ethics of proposing marriage and walimatul ursy according to the opinion of Imam At-Tirmidhi in his Hadith